2016
DOI: 10.1515/jim-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects Induced by Preconditioning with Halogenated Anesthetics

Abstract: backgroundIn the organ transplantation field, a very intense and important topic is to find ways to increase the quality of organs that are taken from willing donors, in order to improve the recovery capacity of the transplant recipients. 1 From the moment of the organ removal until its actual transplantation, there is a variable period of ischemia, named cold-ischemia, responsible for the production Cardioprotective Effects Induced by Preconditioning with Halogenated AnestheticsMarius Papurica 1,2 , Dorel San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the increased vascular resistance leads to an increased motor load of the heart with tachycardia which can lead to hemodynamic collapse [ 16 , 17 , 18 , 19 , 20 ]. It is well-known that one of the pharmacodynamic effects of volatile anesthetics is their impact on the heart function [ 21 , 22 , 23 ], but it should be noted that, apart from its effects on the hemodynamic status, Sevoflurane also has cardioprotective properties. From a molecular point of view, the cardioprotective effects are attained through its action on adenosine triphosphate-sensitive channels which can be found in the cardiac myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the increased vascular resistance leads to an increased motor load of the heart with tachycardia which can lead to hemodynamic collapse [ 16 , 17 , 18 , 19 , 20 ]. It is well-known that one of the pharmacodynamic effects of volatile anesthetics is their impact on the heart function [ 21 , 22 , 23 ], but it should be noted that, apart from its effects on the hemodynamic status, Sevoflurane also has cardioprotective properties. From a molecular point of view, the cardioprotective effects are attained through its action on adenosine triphosphate-sensitive channels which can be found in the cardiac myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20]. It is a known fact that one of the pharmacodynamic effects of volatile anesthetics is their impact on the heart function [21][22][23], but it should be noted that apart from its effects on the hemodynamic status, Sevoflurane also has cardioprotective properties. From a molecular point of view the cardioprotective effects are attained through its action on adenosine triphosphate sensitive channels that can be found in the cardiac myocites.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that these two agents can reduce the levels of reactive species of oxygen, inhibit chemotaxis, and inhibit the activation of neutrophils, leading to decreased neutrophil adhesion to human endothelial cells, decreased IL-6 and TNF-α, suppressed PMN migration and function through various pathways, altered cytokine release from macrophages, and decreased NK cytotoxic activity. A study comparing two anesthetic techniques, TIVA and balanced inhalational anesthesia, found that perioperative cell-mediated immunity was less influenced by TIVA, suggesting that the stress response in patients undergoing anesthesia with a volatile agent is more pronounced [ 102 , 103 , 104 , 105 , 106 , 107 ].…”
Section: Redox Disturbance and Inflammation During General Anesthesia...mentioning
confidence: 99%